Gender and public policies in Latin America: an integral vision of the problem - Sotomayor Gil, Yudith de la Caridad (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2022)
One of the cross-cutting problems in the Latin American scenario is the issue of public policies with a gender focus, which in a climate of implementation of government programs, where the solution to problems of discrimination against women and men is still insufficient, becomes more acute in the COVID-19 framework. Access to resources, education, power relations, among others, is increasingly limited, despite the diversity of institutionalized policies existing in the region that should guarantee equal opportunities and the solution to social differences. That is why this work focuses on explaining the development of public policies in Latin America, emphasizing some countries where difficulties persist in this regard. Techniques such as bibliographic and documentary review are used. Within the methods are:the hermeneutic for from the content analysis to establish the extensive strategy, as part of the component of the quantity-quality criterion, which allows from the understanding and the explanation to arrive to the interpretation that strengthens and rediscovers the objective character of the information, based on the construction of the theoretical data and the case method (empirical level). In this way, an analysis is provided that allows rethinking the different public policies to reverse the situation of gender discrimination and favor conditions that enable social equity in both sexes.
Keywords: public policies; gender; discrimination; equity; transversality